Strength and deformation of encased concrete columns by I- section steel and I- section GFRP subjected to different load conditions - Ban Fadhil Salman; Abbas A. Allawi (Heliyon)
In modern constructions, the use of composite column has become widespread used due to the modern requirements of tall buildings for reducing column cross-sections and construction dead loads. To verify the use of alternative materials employed in construction instead of steel sections, GFRP I-section was utilized in this study for this purpose due to its properties like light weight, corrosion resistance and high strength. The research aims to study the influence of using different types of encased I-section (steel and GFRP) in addition to steel bars in the reinforced concrete composite columns. Twelve rectangular reinforced concrete specimens were tested under varying load conditions. All specimens were divided into three groups depending on the type of material encased. The first group was the reference group, which was reinforced with longitudinal steel bar only. Each group contained four specimens tested under different loading conditions, the first column was subjected to concentric load, the second and third columns were subjected to eccentric loads (e = 25 mm and 50 mm), while the last specimen was subjected to flexural loading (with a two-point load). All the specimens were tested under different loads to investigate composite column behavior and achieve interaction diagram. The experimental findings that columns subjected to concentric load and encased with I -section (steel and GFRP); showed an increase in failure load by 10 % and 8.4 % respectively, relative to reference column. Additionally composite columns tested under eccentric load with eccentricities 25 mm and 50 mm and encased with I -section (steel and GFRP); failure load were increased by 16.6 %, 14.4 %, 25 % and 19.7 % respectively, relative to reference columns. While specimens under flexural load encased with I -section (steel and GFRP); appear that an increase in ultimate load by 81 % and 62 %, respectively, relative to reference specimen. These results show a significant improvement in specimen strength when encased with steel and GFRP. The composite column encased with steel was stronger than column encased with GFRP. Lateral deformation was recorded and show it directly proportion with eccentricity, which increased significantly at an eccentricity of 50 mm. Additionally, analytical results was utilized by FE to emulate the experimental results of the tested specimens, modeling done by using ABAQUS software version 6.14. The FE analysis results display a good agreement with the experimental results for (ultimate strength, strain, modes of failure, lateral and axial deformation) when compared with the experimental specimens.